Writing on steroids? Accuracy of automatic corrective feedback in L2 competence development - Robert Martínez-Carrasco; Alicia Chabert (Bellaterra Journal of Teaching & Learning Language & Literature, 2023)
The article examines the use of written corrective feedback by online grammar checkers as a tool for L2 competence development. While feedback on students’ writing is considered an instrumental part in their learning process, providing comprehensive feedback may not always be possible. Grammar checkers can therefore become an interesting tool to scaffold the students’ learning process as they promote self-directed learning. For the purposes of this study, a set of authentic EFL compositions in English (n=91; C1 CEFR) was subjected to a popular Automated Writing Evaluation (AWE) system, Grammarly, in order to analyse the feedback provided, namely the types and frequency of errors and the level of accuracy in error detection. The findings determine that, while grammar checkers may be useful as a complementary tool, they are developed with native speakers in mind, so the feedback does not always meet the EFL learners’ needs.